Local Wisdom-Based Tourism Village Governance Model To improve the economy in Jambi Province - Tona Aurora Lubis; Erwita Dewi; Fitri Chairunnisa; Muhammad Haris Saputra; Maryati Ningsih (International Journal of Economics, Business and Innovation Research, 2025)
Saturation with modern forms of tourism and the desire to experience life in rural areas again and interact with the community and its socio-cultural activities has led to the development of tourism in rural areas packaged in the form of tourist villages. Tourists who visit are not only interested in the beauty of natural potential but also want to have the opportunity to learn the culture of the area they are visiting. Therefore, tourist villages and local wisdom are two things that synergize with each other. The development of tourist villages is currently still not optimal because it is faced with the obstacles that have been explained previously. One of the crucial obstacles that has the potential to damage the cultural order and life of the community is the degradation of local wisdom. This study aims to formulate a Local Wisdom-Based Tourism Village Governance Model in Jambi Province.This study applies a combination research (mixed method). The combination research used is the Sequential Exploratory Design type, namely the initial stage using qualitative research types, then the second stage using quantitative research types. The objects used in this study were tourist villages in Regencies and Cities in Jambi Province. The results of the study found that the diversity of local wisdom in the form of tourist villages in Jambi Province. Jambi Province has various types of tourist villages based on local wisdom, one of which is the Muaro Jambi Tourist Village and the Seberang Kota Jambi Tourist Village. Meanwhile, this study specifically provides the conclusion that the higher the local wisdom in an area, the higher the performance of the tourist village, Local wisdom is not able to moderate the relationship between tourism village governance and tourism village performance, The higher the governance of tourism villages in an area, the higher the performance of the tourist village